1992
DOI: 10.1111/j.1471-4159.1992.tb10068.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Metabolism in Rat Cortical Astrocyte Cultures

Abstract: Glutamate metabolism in rat cortical astrocyte cultures was studied to evaluate the relative rates of flux of glutamate carbon through oxidative pathways and through glutamine synthetase (GS). Rates of 14CO2 production from [1-14C]glutamate were determined, as was the metabolic fate of [14C(U)]glutamate in the presence and absence of the transaminase inhibitor aminooxyacetic acid and of methionine sulfoximine, an irreversible inhibitor of GS. The effects of subculturing and dibutyryl cyclic AMP treatment of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
2
1

Year Published

1996
1996
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 44 publications
8
94
2
1
Order By: Relevance
“…As the conversion of a-ketoglutarate to glutamate is inhibited almost completely by transaminase inhibitor, the data suggest that glutamate dehydrogenase is not very active in the direction of a-ketoglutarate reductive amination under the conditions used. Several previous reports suggest that glutamate dehydrogenase may not be very active in the oxidative direction (Farinelli and Nicklas, 1992;McKenna et a!., 1993), or in the reductive direction (Yudkoff et al, 1994(Yudkoff et al, , 1996 in rat brain astrocytes, but there is contro- …”
Section: Comentioning
confidence: 97%
See 1 more Smart Citation
“…As the conversion of a-ketoglutarate to glutamate is inhibited almost completely by transaminase inhibitor, the data suggest that glutamate dehydrogenase is not very active in the direction of a-ketoglutarate reductive amination under the conditions used. Several previous reports suggest that glutamate dehydrogenase may not be very active in the oxidative direction (Farinelli and Nicklas, 1992;McKenna et a!., 1993), or in the reductive direction (Yudkoff et al, 1994(Yudkoff et al, , 1996 in rat brain astrocytes, but there is contro- …”
Section: Comentioning
confidence: 97%
“…Investigations of the regulation of glutamate synthesis and breakdown in astrocytes via pathways other than glutaminase and glutamine synthase have shown that astrocytic glutamate is also metabolized via the citric acid cycle after conversion to a-ketog!utarate (Yu et al, 1982;Farinelli and Nicklas, 1992;Westergaard et al, 1995;McKenna et al, 1996a,b). Thus, astrocyticglutamate can be converted to glutamine and exit the cell, or it can be converted to a-ketoglutarate by one of four reversible astrocytic enzymes: glutamate dehydrogenase (Rao and Murthy, 1993;McKenna et al, 1 996b), aspartate aminotransferase (Rao and Murthy, 1993;McKenna et al, 1996b), branched-chain aminotransferase (Yudkoff et al, 1994(Yudkoff et al, , 1996, or alanine aminotransferase (Rao and Murthy, 1993).…”
mentioning
confidence: 99%
“…Interestingly, a marked increase in astrocytic GFAP levels has also been detected in the brain of AD patients (Haga et al, 1989;Ogata et aL, 1992). One of the sites found to have a significantly high GFAP immunoreactivity is neuritic plaque (Farinelli and Nicklas, 1992). It has been suggested that glial cells surrounding neuritic plaques are also involved in the removal of debris from degenerated neurites (Rozemuller et al, 1989;Wisniewski and Wegiel, 1992), the synthesis and deposition of (3-amyloid (Wisniewski and Wegiel, 1992), or the isolation of P-amyloid from neuropil by astrocytic processes (Wisniewski and Wegiel, 1992).…”
Section: IImentioning
confidence: 94%
“…A study with radioactive markers showed that most of the exracellular glutamate is taken up by astrocytes rather then by neurons (McLennan, 1976). The glutamate taken up by astrocytes is then converted by a glia cell-specific enzyme, glutamine synthetase, into glutamine which can, in turn, be used by neurons for glutamate synthesis (Farinelli and Nicklas, 1992). The essential role of astrocytes in protection against glutamate neurotoxicity and maintenance of low extracellular levels of glutamate was further supported by in vitro experiments (Rosenberg et al, 1992).…”
Section: Astrocytic Role In Glutamate and Glucose Metabolismmentioning
confidence: 99%
See 1 more Smart Citation